2014
DOI: 10.1517/14656566.2014.972936
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of trichotillomania (hair pulling disorder): an updated systematic review

Abstract: Early work focused on the serotonin reuptake inhibitors; however, the majority of the trials have been negative. There is a small body of evidence focused on pharmacotherapy for TTM. In future, larger trials are required to expand on the preliminary evidence available for N-acetylcysteine, olanzapine and dronabinol in recent trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Furthermore, fluvoxamine treatment dose of 50 mg/day might be too low for definition of SSRI resistance. It is reported that the existing trials of TTM have very small sample sizes, and the body of evidence is of low quality, mostly clinical trials where a target was more than 18 years old (only one trial included a 16 year-old-subject) [2]. So, the appropriate capacity of fluvoxamine, other SSRI, atypical, or typical antipsychotics for treatment of TTM in children and adolescents is still unknown.…”
Section: Case Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, fluvoxamine treatment dose of 50 mg/day might be too low for definition of SSRI resistance. It is reported that the existing trials of TTM have very small sample sizes, and the body of evidence is of low quality, mostly clinical trials where a target was more than 18 years old (only one trial included a 16 year-old-subject) [2]. So, the appropriate capacity of fluvoxamine, other SSRI, atypical, or typical antipsychotics for treatment of TTM in children and adolescents is still unknown.…”
Section: Case Presentationmentioning
confidence: 99%
“…TTM is associated with distress as well as with social and occupational impairment [1]. Accumulating evidence suggests that pharmacotherapy with selective serotonin reuptake inhibitors (SSRIs), tricyclic antidepressants (TCAs), antipsychotics, opioid-antagonists, or glutamate modulators has the potential to improve TTM in adults [2]. Recent empirical studies have also pointed to the potential of cognitive behavioral therapy (CBT) for the treatment of childhood TTM [3].…”
Section: Introductionmentioning
confidence: 99%
“…But, a significant stressful life event was not detected in this case. Although SSRIs continue to be used for therapeutic purposes in cases of trichotillomania, the results from studies regarding its effectiveness are negative [17]. Indeed, trichotillomania was reported to develop in association with fluoxetine use in a 7year-old boy [7], and exacerbation of trichotillomania symptoms with fluoxetine use was also reported in a girl of the same age to be [18].…”
Section: Discussionmentioning
confidence: 99%
“…Selective serotonin reuptake inhibitors, in general, show negative results and, in case reports, have been potentiated with atypical antipsychotics. Despite their widespread use, they do not appear to be effective in trials, particularly in monotherapy 26,[30][31][32]34 are presented in Table 4.…”
Section: Secondary Psychiatric Disordersmentioning
confidence: 99%